USING INNOVATION AND ACTION RESEARCH TO BUILD TESOL TEACHER CAPACITY IN VIETNAM - Andrew, Martin Benedict (Universitas Negeri Makassar, 2017)
Critical insights from educational innovation research inform TESOL educators in Vietnam that pedagogical interventions should be particular to their context and environment. This paper presents a qualitative descriptive analysis of four teachers who are students in a Master of Education (TESOL) program delivered in Vietnam by within a partnership between an Australian and a Vietnamese University. The study draws on the assessed work of students in the unit Innovation which aims to encourage its students, all of whom are experienced professional educators, to identify a research problem specific to their teaching and learning environment and design a research question built around a pedagogical or curricular intervention they can ethically implement and evaluate within their workplaces. This activity, serving as both curriculum and assessment, empowers students to apply a segment of an action research cycle to their classrooms. The study presents four narratives of teacher/researchers engaged in innovation research, identifying research problems, developing topics and lines of enquiry and ultimately evaluating their projects reflectively. This pedagogical approach articulates the idea that the best people to know what innovations are required in Vietnamese educational contexts are the teachers themselves. Additionally, the findings support the use of an action research-focused pedagogy as an appropriate approach for use in TESOL programs in such developing nations as Vietnam.